Empty sella Syndrome as a Cause of Hypopituitarism Case study - Ahmed, Yousif Baha'addin (Diyala Journal of Medicine, 2018)
Background:Empty sella syndrome is the radiological appearance of an enlarged or deformed sella turcica which is partially or completely filled with cerebrospinal fluid .In 20-50% of patients there may be endocrinologic dysfunction, pan hypopituitarism is present in 25% of cases and isolated one in 10%. Objective: To present a patient in with features of hypopituitarism caused by empty sella syndrome, with related literature review. Patients and Methods: A Case of 16 years adolescent male was presented with short stature, the height of the patient was less than 3% percentile for his age and sex, weakness, and lack of secondary sexual characters and delayed puberty due to empty sella syndrome, the patient has deficiency of all important anterior pituitary hormones in addition to corresponding target hormones, total hypopituitarism is the diagnosis and it is the cause of short stature. Results: He has delayed puberty , the laboratory findings of the patient clearly indicate pan hypopituitarism and the MRI confirmed empty sella syndrome. Conclusion: Empty sella syndrome can cause panhypopituitarism, and adequate pituitary imaging is required for cases with isolated pituitary hormone deficiency or panhypopituitarism.